UPAYA PENINGKATAN KAPASITAS UMKM MELALUI PENERAPAN SOCIAL MEDIA MARKETING - Suharyati, Suharyati; Ediwarman, Ediwarman; Handayani, Tati (Batara Wisnu : Indonesian Journal of Community Services, 2021)
The global pandemic of covid disease, covid-19, has caused the world's economic growth and Indonesia's to decline. The positive impact of the Covid-19 pandemic is that it encourages all business actors to fight for the survival of their companies. The rapid advancement of technology can be used to market MSME products to various corners of consumers online. Improving the quality of human resources and information technology is necessary to adapt to various technologies that have emerged in the era of the industrial revolution 4.0. Community service activities with the theme "Efforts to Increase MSME Capacity Through the Application of Social Media Marketing" were carried out in Duren Mekar village, Bojongsari sub-district, Depok City, aiming to provide training and assistance in marketing products or services through social media. 34 MSME attended this activity. The participant's business fields consist of essential food, culinary, fashion, and handicraft businesses. Types of social media used as product marketing media in Whatsapp: 57.6%; Facebook: 22%; Instagram: 16.9%; Twitter: 1.7%; TikTok:1.7%. These results indicate that the use of social media is still not optimal as a means of marketing products or services as a cheap marketing medium. After training the participants on the application of social media marketing, based on the questionnaire results, it shows that the percentage (%) level of understanding reaches 89.7%. These results explain that after training on social media marketing, participants understand the training material provided. For this reason, it is necessary to carry out ongoing training so that participants can apply it as a marketing strategy to increase sales